О приближении плоской волны в расчётах проникновения электромагнитного поля в тонкие проводящие оболочки - Бондина, Н.Н.; Михайлов, В.М. (Електротехніка і електромеханіка, 2011)
Conditions of plane wave approximation validity in computation of electromagnetic field penetration into thin conductive shells with non-planar boundary surfaces are formulated. Criterial analysis of the approximation errors as compared with analytical solutions for ordinary-shape shells is made.